UZBEK NATIONAL COSTUME OF KASHKADARYA- SURKHANDARYA IN THE EARLY XIX-XX CENTURIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article provides information about the history, social origin, types of clothing parts and their ethnic significance, meaning, and use in traditional ceremonies of the Kashkadarya-Surkhandarya Uzbek national costume. Studies have been conducted on their similarities and differences.